State programs for the development of genetic technologies - Zarina N. Bedoeva, Saria B. Nanba, Oganes A. Akopyan, Emil V. Alimov, Maria A. Garmaeva, (Opción, 2020)
The article analyzes state programs for introducing genetic technologies, their goals and development prospects via comparative qualitative research methods. As a result, the Human Genome Project had a significant impact, the completion of which coincided with the development of computer technology. In conclusion, now humankind is at the beginning of a new era, which opens up new prospects for maintaining human health. This is facilitated by the use of genetic testing in personalized medicine. That is why federal and international programs for the introduction of genetic technologies require approval.